Effects of dietary cottonseed oil and tannin supplements on protein and fatty acid composition of bovine milk. Issue 2 (5th March 2014) - Aprianita, Aprianita; Donkor, Osaana N; Moate, Peter J; Williams, S Richard O; Auldist, Martin J; Greenwood, Jae S; Hannah, Murray C; Wales, William J; Vasiljevic, Todor
Abstract : This experiment was conducted to determine the effects of diets supplemented with cottonseed oil, Acacia mearnsii -condensed tannin extract, and a combination of both on composition of bovine milk. Treatment diets included addition of cottonseed oil (800 g/d; CSO), condensed tannin from Acacia mearnsii (400 g/d; TAN) or a combination of cottonseed oil (800 g/d) and condensed tannin (400 g/d; CPT) with a diet consisting of 6·0 kg dry matter (DM) of concentrates and alfalfa hay ad libitum, which also served as the control diet (CON). Relative to the CON diet, feeding CSO and CPT diets had a minor impact on feed intake and yield of lactose in milk. These diets increased yields of milk and protein in milk. In contrast to the TAN diet, the CSO and CPT diets significantly decreased milk fat concentration and altered milk fatty acid composition by decreasing the proportion of saturated fatty acids but increasing proportions of monounsaturated and polyunsaturated fatty acids. The CPT diet had a similar effect to the CSO diet in modifying fatty acid profile. Overall, reduction in milk fat concentration and changes in milk fatty acid profile were probably due to supplementation of linoleic acid-rich cottonseed oil. The TAN diet had no effect on feed intake, milk yield and milk protein concentration. However, a reduction in the yields of protein and lactose occurred when cows were fed this diet. Supplemented tannin had no significant effect on fat concentration and changes in fatty acid profile in milk. All supplemented diets did not affect protein concentration or composition, nitrogen concentration, or casein to total protein ratio of the resulting milk.